2019
DOI: 10.1097/sla.0000000000002439
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Carcinoma In Situ and Margins <2 mm

Abstract: Routine additional surgery may not be justified for patients with negative margins <2 mm who undergo RT but should be performed in patients who forego RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…[19] However, specifically for women who did not receive RT, in this series there was an association between a DCIS margin of <2mm and ipsilateral breast recurrence. This provides direct evidence in support of more recent reviews, meta-analysis and consensus guidelines [20,21] as well as recent studies [22].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[19] However, specifically for women who did not receive RT, in this series there was an association between a DCIS margin of <2mm and ipsilateral breast recurrence. This provides direct evidence in support of more recent reviews, meta-analysis and consensus guidelines [20,21] as well as recent studies [22].…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, patients not receiving RT had a higher (7.2%) breast recurrence rate, confirming patient selection for RT could be improved. [22] Endocrine therapy was associated with a non-significant reduction in ipsilateral breast recurrence independent of RT, although the greatest effect was seen for the reduction of invasive further events in the absence of RT. In a contemporary analysis of the US retrospective National Cancer Data Base (70% of the US population), 36.5% of women (most commonly between 50 and 59 years of age) received adjuvant endocrine therapy for DCIS [23] compared with 12.2% in this UK-based study, and no-one in a cohort in the Netherlands [12], reflecting the inconsistent interpretation of evidence from trials examining the impact of endocrine therapy for DCIS on local recurrence, the associated toxicities and issues of adherence to adjuvant tamoxifen treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported that women with clear margins after surgery for DCIS have lower rates of local recurrence than do women who have involved margins,12232425 as does our study. Although guidelines recommend that margin widths do not need to be more than 1 or 2 mm,2226 our study suggests that having margins greater than this may confer some further benefit.…”
Section: Discussionsupporting
confidence: 73%
“…As discriminating the two tissue types with DRS seems impossible, this might have implications for what is detected by DRS as a positive resection margin. Importantly, there is ongoing controversy around the current definition of a positive resection margin for DCIS and this could further shift towards an even more liberal definition in the future [ 5 , 39 42 ]. There are some indications that a less stringent interpretation of a positive resection margin is safe for DCIS as long as post-operative radiotherapy is not omitted [ 43 ].…”
Section: Discussionmentioning
confidence: 99%